Political Parties Re-Disconnected? Websites and Social Media of Indonesian Political Parties - Gilang Desti Parahita; Nella Aprilia Puspitasari (Jurnal InterAct, 2014)
Political parties of Indonesia today have created their own websites in which the patterns of the use of ICT (Information and Communication Technology) by political parties are much affected by the political and media system (Anstead and Chadwick, 2010; Ward and Gibson, 2010). What are the patterns of Indonesian political parties in utilizing websites for their political communications? The political culture, digital divides, and media system have shaped the practices of websites and social media of political practices. In the previous environment of media, citizens were disconnected from the membership of Indonesian political parties. New media, instead of giving more ways to let netizens engage and participate in political parties’ activities, treats netizens, once again, merely as passive parties’ message consumers. In other words, political parties are re-disconnected from their constituents after its first disconnection: the massive use of television for political campaign and the loose political membership.The research then concludes that the political parties in Indonesia tend to employ a cartel party strategy through online communication as coined by Löfgren and Smith (2003). The web practices of political parties are more concentrated on informing prior to and during the political campaign period. By contrast, involving and connecting the supporters are shown less in both periods. Social media are expected to be more involving and opening up online forums during the campaign period. However, though interactivity occurs in some degrees, the vertical interactivity was happening less compared to the horizontal one, which, in this case, is also more prone to endorse less substantial comments.